Hand Foot Syndrome Secondary to Low Dose Docetaxel - Tunio, Mutahir A; Al Asiri, Mushabbab; Durrani, Sajid Khan (International Journal of Health Sciences, 2015)
Hand-foot syndrome (palmoplantar erythrodysesthesia or Burgdorf reaction), is a distinctive skin toxicity affecting the palms and soles after certain chemotherapeutic drugs. Docetaxel induced hand-foot syndrome is rare, dose-dependent adverse event. Here in we report a case of Docetaxel induced grade III hand-foot syndrome at low doses (75/m2). Â Key words: Hand-foot syndrome, Docetaxel, low dose